A simple visual analog scale for pain is as responsive as the WOMAC, the SF-36, and the EQ-5D in measuring outcomes of revision hip arthroplasty. (April 2014) - Zampelis, Vasilis; Ornstein, Ewald; Franzén, Herbert; Atroshi, Isam
<x xml:space="preserve">Abstract</x> Background and purpose — Little is known about the comparative performance of patient-reported outcome measures in revision hip arthroplasty. We compared the performance of the WOMAC, the SF-36, the EQ-5D, and a pain-related visual analog scale (VAS) in revision hip arthroplasty. Methods — 45 patients with aseptic prosthetic loosening following primary hip arthroplasty completed the WOMAC, the SF-36, the EQ-5D, and a VAS for pain—at baseline and 2 years after revision. Responsiveness of the measures was compared with the effect size (with ≥ 0.8 being considered large). Agreement between scales measuring the same type of outcome (pain or physical function) was assessed with the Bland-Altman method. Results — The mean preoperative scores for the pain and physical function scales of WOMAC and SF-36, EQ-5D index, and VAS for pain improved statistically significantly 2 years after revision. The effect size for the WOMAC pain was 1.7, that for SF-36 pain was 1.4, that for WOMAC physical function was 1.6, that for SF-36 physical function was 0.8, and that for EQ-5D index was 1.2. The VAS for pain had an effect size of 2.1, which was larger than that for SF-36 pain and for the EQ-5D index (p ≤ 0.03) but not for WOMAC pain (p = 0.2). The limits of agreement between WOMAC pain, SF-36 pain, and the VAS scale measuring pain—and between the WOMAC and SF-36 scales measuring physical function—were wide. Internal-consistency reliability was high for the WOMAC and SF-36 scales but low for the EQ-5D. Interpretation — In patients with first-time revision hip arthroplasty done for aseptic loosening, the WOMAC, SF-36, and EQ-5D showed high responsiveness in measuring patient-reported outcomes and the simple VAS for pain performed equally well.